Sector-level strategies against precarious employment in Germany: Evidence from construction, commercial cleaning, hospitals and temporary agency work - Thorsten Schulten; Karin Schulze-Buschoff (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2015)
This study focuses on describing and analyzing the concrete initiatives taken by trade unions and employers to combat precarious employment. It is based on an evaluation of recent data, research literature and policy documents as well as a number of interviews with experts from all four sectors. The study is also part of a wider European project called "Bargaining for Social Rights at Sector Level" (BARSORIS) which include studies from seven European countries (Denmark, Germany, Italy, Netherlands, Slovakia, Spain and the UK).
Keywords: 330